2016
DOI: 10.1002/mds.26499
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar ataxia in progressive supranuclear palsy: An autopsy study of PSP‐C

Abstract: Background Cerebellar ataxia is an exclusion criterion for clinical diagnosis of progressive supranuclear palsy (PSP), but a variant with predominant cerebellar ataxia has been reported. The aims of this study were to estimate the frequency of PSP with predominant cerebellar ataxia in an autopsy series from the United States, and to compare clinical, pathologic, and genetic differences between PSP with and without predominant cerebellar ataxia. Methods We selected 100 consecutive patients with pathologically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 40 publications
1
39
1
1
Order By: Relevance
“…In contrast to the ratio of three out of 22 consecutive patients reported in an earlier Japanese study, a recent Western autopsy study identified only 5 PSP-C in 1,085 pathologically confirmed PSP cases, four of which were clinically misdiagnosed as MSA-C. 23 Clinical features of PSP-C were similar to those of MSA-C, but lacking marked dysautonomia sufficient to meet criteria for a clinical diagnosis of MSA. 23 Because PSP-C is difficult to diagnose during life and ataxia is far more often suggestive of other neurodegenerative diseases rather than PSP, this variant is not included in the new MDS PSP criteria.…”
Section: Symptomatic Psp Phenotypesmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast to the ratio of three out of 22 consecutive patients reported in an earlier Japanese study, a recent Western autopsy study identified only 5 PSP-C in 1,085 pathologically confirmed PSP cases, four of which were clinically misdiagnosed as MSA-C. 23 Clinical features of PSP-C were similar to those of MSA-C, but lacking marked dysautonomia sufficient to meet criteria for a clinical diagnosis of MSA. 23 Because PSP-C is difficult to diagnose during life and ataxia is far more often suggestive of other neurodegenerative diseases rather than PSP, this variant is not included in the new MDS PSP criteria.…”
Section: Symptomatic Psp Phenotypesmentioning
confidence: 70%
“…1,14 Other vPSP syndromes named according to their predominant clinical features may account for about one third of earlier presentations in aggregate and include PSP with predominant parkinsonism (PSP-P), 16 pure akinesia with gait freezing (formerly PAGF, now PSP-PGF), 17 corticobasal syndrome (PSP-CBS), 14,18 primary progressive apraxia of speech or non-fluent variant primary progressive aphasia (nfvPPA; when caused by PSP: PSP with predominant speech/language disorder or PSP-SL), 1921 behavioral variant frontotemporal dementia (bvFTD, when caused by PSP: PSP with predominant frontal presentation or PSP-F), 14,22 and PSP with predominant cerebellar ataxia (PSP-C) (Figure 2). 23 …”
Section: The Clinical Spectrum Of Pspmentioning
confidence: 99%
“…Immunohistochemistry for phospho‐tau (CP13, 1:1000, from Dr. Peter Davies, Feinstein Institute, North Shore Hospital, NY) was used to establish neuropathological diagnosis of PSP . The regional tau burden, including pretangles/NFT, coiled bodies, tufted astrocytes, and tau‐positive threads, was graded semiquantitatively on a 4‐point scale (0 = absent, 1 = sparse, 2 = moderate, and 3 = frequent) . Select sections were processed for Gallyas silver stain and immunohistochemistry for 4‐repeat tau (RD4, 1:5,000; Millipore, Temecula, CA) to assist in neuropathological diagnosis of AGD .…”
Section: Methodsmentioning
confidence: 99%
“…We assessed clinical information in all PSP‐TDP cases and a subset of TDP‐43‐negative PSP cases (N = 88). The latter group was described as the Mayo Clinic patient series in our previous reports . Ante‐mortem clinical information for age at onset, clinical diagnosis, cognitive impairment, the last available Mini–Mental State Examination (MMSE) scores, and the duration between MMSE performed and death were gathered from clinical reports and/or a brain bank questionnaire filled out by a close family member.…”
Section: Methodsmentioning
confidence: 99%
“…Morris et al described patients with PSP who resembled idiopathic Parkinson's disease (PSP‐P) . Other PSP variants/phenotypes with a predominantly subcortical burden of tau pathology have been recognized and include primary progressive freezing of gait (PGF), PSP with postural instability, and PSP with predominant cerebellar ataxia . Recognition of these diverse phenotypes in autopsy‐proven cohorts led to the development of the International Parkinson and Movement Disorder Society (MDS) criteria for diagnosis of PSP (Supplementary Table 1).…”
mentioning
confidence: 99%